Analysis of real-time ship manoeuvring simulation with a ship collision avoidance E-navigation aid system - Kun-Yuan Tsai; Chih-Chung Fang (International Journal of Naval Architecture and Ocean Engineering)
This study aims to develop a smart navigation database for ship manoeuvring based on real-time simulations in calm water. In the ship manoeuvring simulation, the entry of a large container ship into the Kaohsiung and Keelung harbours is executed by different marine mates by using the PC version of the real-time ship simulator. First, multiple real-time simulations are conducted for each harbour, and qualitative analyses are performed based on relevant statistics. Furthermore, the ship collision avoidance E-navigation-aid system developed by the authors is used to assist the five marine mates in entering the Kaohsiung and Keelung harbours, and the differences between the scenario in which the mates are assisted by the system and that in which they perform manual operation are discussed. Finally, based on simulation statistics, comparisons of voyage time, voyage distance, and rudder operation with and without the ship collision avoidance E-navigation-aid system are presented and discussed.